A 4-Year cross-sectional study of Hepatitis B virus infection among pregnant women: need for policy decision (2022)
Background: The elimination of hepatitis B virus (HBV) in Nigeria, especially among pregnant women requires commitment from the government and health policy makers. This is predicated on comprehensive surveillance and epidemiological data. The objective of the current study is to provide the epidemiological data and unique perspectives that will inform accurate advocacy and influence policy decisions. Materials and Methods: A 4-year cross-sectional study was conducted among 2,428 consecutively recruited consenting pregnant women attending antenatal care at the University College Hospital, Ibadan, Oyo State, Nigeria. Venous blood was screened for HBsAg using Enzyme Linked Immunosorbent Assay (ELISA). HBsAg sero-negative samples were further tested for other HBV serological markers (anti-HBc, HBeAg and anti-HBe by ELISA. Socio-demographic and clinical details were obtained using a semi-structured questionnaire. Results: Overall HBsAg prevalence was 5.1% (2,305/2,482). Twenty three (1%) of the HBsAg sero-negative women tested positive to both anti-HBc and anti-HBe while 5.3% and 0.8% tested positive to only anti-HBc and anti-HBe, respectively. Additionally, 6.4% (38/594) of the HBV fully vaccinated pregnant women tested positive to HBsAg. Conclusion: Hepatitis B is endemic among Nigerian pregnant women. Serological patterns indicated possible occult hepatitis B infection. More political commitment from government and policy makers is urgently required.